USAHA GURU PENDIDIKAN AGAMA ISLAM DALAM MENCEGAH DAN MENGATASI PERILAKU MENYIMPANG SISWA MTs.MA'ARIF NU 02 KECAMATAN BRUNO KABUPATEN PURWOREJO - Rafiq Ridho (FAI UMY, 2014)
This study aims to describe the kinds of deviant behavior and the factors that influence it , and to know the efforts of Islamic religious education teachers in preventing and addressing student misconduct MTs . Maarif NU 02 Bruno Bruno District of Purworejo district and the results of the work done . The type of this research is qualitative research subjects Islamic religious education teacher . The method of data collection is done by observation , interviews , and documentation . While the analysis of qualitative data using isdeskriptifanalysts . This qualitative descriptive analysis is used to generate the data deskripstif form of interviews and observations of the parties interviewed and observed .The result of this study is there are various kinds of deviant behavior of the student MTs .Maarif NU 02 Bruno include ditching , carrying electronic goods terlatang , courtship that exceed the limits , smoking , late , ngepil , and disrespectful to the teacher . It is influenced by internal factors and external factors . The work done Islamic religious education teachers in preventing and addressing student misconduct has been very effective , as students become better behaved , and about 80 percent of cases resolved despite some irregularities were handled relatively heavy.